Dynamics of disability in the adult population of the Astrakhan region due to diseases of the cardiovascular system over 2016–2022 - E. B. Starodubova; E. N. Chernysheva; A. A. Svetlichkina; V. V. Svinskayte (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2024)
In the structure of primary disability pathologies of the cardiovascular system hold second position in the Astrakhan region. The article presents statistical indicators of primary and repeated disability of the population in the Astrakhan region due to diseases of the cardiovascular system from 2016 to 2022. Analysis of the structure of primary disability indicates that among the study population in the Astrakhan region there was a higher proportion of disabled people of group III. Elderly disabled people are in first place in the age structure of primary disability due to diseases of the cardiovascular system.